Computer models offer new insights into the mechanics of rock climbing - Russell, S. D.; Zirker, C. A.; Blemker, S. S. (Sports Technology, 2012)
Three computer models of varying complexity were developed in order to investigate the kinematics, kinetics, muscle operating ranges, and energetics of rock climbing. First, inverse dynamic models were used to investigate the joint angles and torques used in climbing and to quantify the total mechanical work required for typical rock climbing. Climbing experience was found to have a significant effect on the kinematics used in climbing; however, there were no significant differences in mechanical work. Second, a musculoskeletal model of the whole body was developed, this model combined with the kinematic data was used to analyze the operating ranges of the upper and lower limb muscles during climbing. In general, the experienced climbers employed kinematic motions that corresponded to muscle fibers used for climbing operating much closer to their optimum length than the kinematics of inexperienced climbers. Third, a forward dynamic model was developed to predict the metabolic goal of climbing. The results of this model suggest that an experienced climbing style minimizes the fatigue of muscles while an inexperienced climbing style minimizes the total joint torques generated.